EVALUASI STATUS KESUBURAN TANAH PADA BEBERAPA JENIS PENGGUNAAN LAHAN DI DESA PENGERAGOAN, KECAMATAN PEKUTATAN, KABUPATEN JEMBRANA - I GUSTI AYU SURYA UTAMI DEWI; I WAYAN SUKASANA (GANEC SWARA, 2024)
This research was carried out in Pengeragoan Village, Pekutatan District, Jembrana Regency, from July to September 2023. The aim of this research was to determine the chemical properties of soil and determine soil fertility status classes and provide direction in land management according to the level of soil fertility status for each type. Land use in Pengeragoan Village, Pekutatan District, Jembrana Regency. The types of land use that exist include coffee plantations, cocoa plantations, coconut plantations, mixed plantations, natural forests, teak forests and rice fields. Sampling was carried out compositely on several existing land use types, namely coffee plantations (Tki), cocoa plantations (Tko), coconut plantations (Tka), mixed plantations (Tc), natural forests (Tha), teak forests (Tj), and rice field (Ts). Determination of soil fertility status is carried out by measuring soil chemical properties parameters, namely soil Cation Exchange Capacity (CEC), Base Saturation (KB), P-total, K-total and C-organic. The research results show that the soil fertility status in several types of land use falls into the criteria of high, medium and low. Natural forest and mixed garden land use types have high soil fertility status. The land use types of coffee plantations, cocoa plantations and teak forests have medium soil fertility status. The land use types of coconut plantations and rice fields have low soil fertility status. The management direction recommended from the results of evaluating soil fertility status and several supporting soil chemical properties for each type of land use is the need to add N and P nutrients to the land use types of coffee plantations, mixed plantations and natural forests. In the types of land use of cocoa plantations, coconut plantations, teak forests and rice fields, it is necessary to add nutrients N, P and organic materials in the form of plant litter and organic fertilizer.